Key Elements of Leadership 5.0 Within Inter-Organizational Networks – Attempts to Specify Future Research Areas - Michał Organa (Communications of International Proceedings, 2025)
This article focuses on the growing need for modern leadership models that support coordination and value creation in complex interorganizational networks, currently shaped by advanced digital technologies. Despite the growing interest in Leadership 5.0, research results are scarce, and current research processes – due to the concept's initial stage of development – remain fragmented and incomplete. A coherent framework explaining the specific roles and types of influence of leaders in networked and ecosystem environments is still lacking. This article adopts a conceptual research approach based on an integrated synthesis of literature on the thematic areas of leadership, interorganizational networks, and the guiding principles of Industry 4.0 / 5.0 and Society 4.0 / 5.0. The main contribution is the development of a conceptual framework for Leadership 5.0 embedded in the conditions of interorganizational networks. The proposed framework identifies five key orientations of Leadership 5.0: human-centricity, digital innovation, network-ecosystem, sustainability-resilience, and technological-social competence. Collectively, these orientations emphasise the multidimensional, comprehensive, and integrative nature of contemporary leadership in complex collaborative systems. This provides a rational basis for future empirical research on the impact of leadership in interorganizational networks.
Keywords: 5.0 leadership; network leadership; human-centric leadership; Industry 4.0; Industry 5.0; Society 4.0; Society 5.0